Recent Advances in Novel Modulators for Cardiac Myosin Disorders - Wang, Hancheng; Wang, Mengfei; Han, Bo; Chen, Qiushi; Zhang, Qingwei (Pharmaceutical Fronts, 2025)
In advanced stages of heart disease, most cases are characterized by heart failure, where the heart's systolic and diastolic functions are weakened, and then it cannot meet the body's normal oxygen demands. The contraction of the heart, at the molecular level, involves the interaction between thick filaments (primarily composed of myosin) and thin filaments (primarily composed of actin), where adenosine triphosphate is used as an energy source to generate contraction force. In view of this, cardiac myosin may be a crucial target for the regulation of heart-related diseases. In 2022, mavacamten was approved by the Food and Drug Administration as a first-in-class myosin modulator for the treatment of obstructive hypertrophic cardiomyopathy. At the same time, there is continuing evidence that indicates cardiac myosin modulators as potential agents for the treatment of a variety of cardiac conditions. This review summarizes the current discovery, design, and indication of cardiac myosin modulators to provide valuable insights for further drug development in related fields.
Keywords: obstructive hypertrophic cardiomyopathy; mavacamten; cardiac myosin modulators